Kerma coefficients for neutron scattering on12C and16O at 96 MeV - P. Mermod (2018)
Recently, many new applications of fast neutrons are emerging or under development, like dose effects due to cosmic ray neutrons for airplane crew, fast neutron cancer therapy, studies of electronics failure induced by cosmic ray neutrons and accelerator-driven incineration of nuclear waste and energy production technologies. In radiation treatment, the kerma (Kinetic energy release in matter) coefficient, which describes the average energy transferred from neutrons to charged particles, is widely used. The kerma coefficient can be calculated from microscopic nuclear data. Nuclear data above 20 MeV are rather scarce, and more complete nuclear data libraries are needed in order to improve the understanding of the processes occurring on a cellular level. About half the dose in human tissue due to fast neutrons comes from proton recoils in neutron-proton (np) scattering, 10-15% from nuclear recoils due to elastic and inelastic neutron scattering and the remaining 35-40% from neutron-induced emission of light ions. Experimental data on elastic and inelastic neutron scattering at 96 MeV from12C and16O have been obtained recently at The Svedberg Laboratory in Uppsala, Sweden. These data are shown to be relevant for the determination of nuclear recoil kerma coefficients from elastic and inelastic neutron scattering at intermediate energies. © The Author 2007. Published by Oxford University Press. All rights reserved.